Qualitative inquiry & research design : choosing among five approaches - Creswell, John W.; Poth, Cheryl N. (Los Angeles : SAGE, 2018)
This book explores the philosophical underpinnings, history, and key elements of five qualitative inquiry approaches: narrative research, phenomenology, grounded theory, ethnography, and case study. The authors compare the approaches and relate research designs to each of the traditions of inquiry in a highly accessible manner. Featuring new content, articles, pedagogy, references, and expanded coverage of ethics throughout, the book is an introduction to the theories, strategies, and practices of qualitative inquiry.
Philosophical assumptions and interpretive frameworks -- Designing a qualitative study -- Five qualitative approaches to inquiry -- Five different qualitative studies -- Introducing and focusing the study -- Data collection -- Data analysis and representation -- Writing a qualitative study -- Standards of validation and evaluation -- "Turning the story" and conclusion.
Includes bibliographical references (pages 423-438) and indexes.
ENH
Trim Education, R. K. Corporation
Keywords: Social sciences -- Methodology; Research -- Design; Qualitative Research; Research Design; English language